Diurnal, vertical, and among sampling days variation of dissolved O2 , CO2 , and pH in a shallow, tropical reservoir (Garças reservoir, São Paulo, Brazil) (2003)
ABSTRACT: Sampling of physical, chemical, and biological variables was performed at a single station at Garças reservoir in five depths at four-hour intervals during summer (3-4 March), fall (13-14 June), winter (29-30 August), and spring (29-30 November) of 1994. Dissolved oxygen, dissolved inorganic carbon forms, pH, and total alkalinity were measured. During the summer, dissolved O2 was present in low concentrations and showed a diurnal variation of about 2.65 times greater than vertical spatial variation. The lowest diurnal variation of oxygen occurred during the winter sampling period and t he highest variation in the spring. During the spring, vertical variation of O2 was lower than in winter; diurnal variation was less than vertical variation and was not significantly different. During fall, CO2 concentrations were lower than in the summer. Because of the uniformity of thermal profiles, diurnal variation of CO2 was not evident during winter and spring. During the latter season, there was an increasing use of HCO3 - as the CO2 source for photosynthesis during the Microcystis bloom. Vertical variation of total CO2 was significant during winter and spring sampling days, mainly in the spring. Lack of significant vertical variation during summer and fall was most likely due to mixing of the water column. Differences in mean pH values were only significant during fall and winter. pH value increases were associated with the continuous CO2 demand for photosynthesis of the Microcystis Bloom.